Distance Protection Algorithm based on alpha/beta/0-components and Delta Quantities for Getting Insensitive against Power Swings - Jaworski, Michael; Jäger, Johann; Lorz, Tobias (The 15th IET International Conference on Developments in Power System Protection, 2020)
The stabilisation of the distance protection function against inappropriate trip responses due to power swings represents the main topic of this paper. In today's power grids, this problem is covered by the implementation of power swing blocking functions. However, this function is only a corrective add-on algorithm and not an integral part of the distance function itself. This leads to the fact, that symmetrical short-circuits followed up by a power swing are subjected to strongly reduced backup protection dependability from the upstream distance relays. The aim of creating a distance algorithm, which offers inherent power swing insensitivity instead of using a power swing blocking function, is achieved by applying the Δ-quantities of the αβ0-components of voltage and current. Beginning with the basics of the proposed distance algorithm up to a suitable relay logic, the all-important parts of the Δ21 relay are provided and discussed in this paper. Finally, a study case provides the platform for its performance evaluation.<br
Keywords: delta quantities; distance protection; Power swing; power system restoration; αβ0-components